Cross-Cloud Data Consistency Models for Always-On Banking Platforms (International Journal of Engineering & Extended Technologies Research (IJEETR), 2024)
Banking on-demand portals need to be operational 24/7 without loss of high-quality transactional integrity in multisite distributed clouds. This paper is a quantitative analysis of the cross cloud data consistency models such as strong, eventual and the hybrid approaches. We experiment with availability, latency, violation rate, and ratio of degradation with injected network partitions and regional outages under the realistic banking loads of payment processing, account management and fraud detection. The findings demonstrate definite trade-offs of rightness and correctness. Models Hybrid consistency models offer a middle ground between consensus protocols and CRDT-based replication by allowing a resilient and scalable banking system that is satisfactory both operationally and effectively regulated.
Keywords: Cross-Cloud Computing; Data Consistency Models; Strong Consistency; Eventual Consistency; Hybrid Consistency